2016
DOI: 10.1530/rep-16-0342
|View full text |Cite
|
Sign up to set email alerts
|

Sperm of patients with severe asthenozoospermia show biochemical, molecular and genomic alterations

Abstract: The multifactorial pathological condition, that is, severe low sperm motility is a frequent cause of infertility. However, mechanisms underlying the development of this condition are not completely understood. Single abnormalities have been reported in sperm of patients with asthenozoospermia. In this study, we characterized, in 22 normozoospermic men and in 37 patients with asthenozoospermia, biochemical, molecular and genomic abnormalities that frequently occur in sperm of patients with asthenozoospermia. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 52 publications
7
45
0
Order By: Relevance
“…To overcome of these imbalances, researches tried to improve in vitro supplementation with antioxidant activity or some necessary element that participated in procedure that lead to maintain spermatozoa in functional and healthy condition (Banihani, Sharma, Bayachou, Sabanegh, & Agarwal, ; Im Yun, Gong, Song, & Lee, ). Previous studies revealed that spermatozoa from asthenoteratozoospermic men have increased the rate of membrane lipid peroxidation and DNA fragmentation and decreased MMP than normal fertile men (Abad et al., ; Bonanno et al., ; Colagar et al., ). Our descriptive data were in agreement with these studies (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…To overcome of these imbalances, researches tried to improve in vitro supplementation with antioxidant activity or some necessary element that participated in procedure that lead to maintain spermatozoa in functional and healthy condition (Banihani, Sharma, Bayachou, Sabanegh, & Agarwal, ; Im Yun, Gong, Song, & Lee, ). Previous studies revealed that spermatozoa from asthenoteratozoospermic men have increased the rate of membrane lipid peroxidation and DNA fragmentation and decreased MMP than normal fertile men (Abad et al., ; Bonanno et al., ; Colagar et al., ). Our descriptive data were in agreement with these studies (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent increased mitochondrial copy number may lead to hypospermatogenesis due to meiotic arrest during sperm development and/or a disorganised axonemal complex as evidenced by asthenozoospermia (Feng, Song, Zou, & Mao, ). Additionally, in patients with asthenozoospermia, spermatozoa show significant increase in mtDNA copy number when compared to that of controls (Bonanno et al., ). Normally, there is minimal contribution of paternal mtDNA to the genome of an embryo as it is quickly eliminated in early embryonic development (May‐Panloup et al., ; reviewed in Benkhalifa et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, elevated ROS exposure leads to membrane damage, membrane instability and functional alterations causing cell death (Agarwal et al., ). Latest evidence demonstrates an association between high ROS levels and increased mitochondrial DNA (mtDNA) copy number with decreased mtDNA integrity (Bonanno et al., ). Oxidative stress (OS) occurs when there is an imbalance between oxidants and antioxidants (Agarwal, Hamada, & Esteves, ).…”
Section: Introductionmentioning
confidence: 99%